Integration of soft skills in nursing clinical evaluation: a narrative analysis - Wan Idris, Wan Umi Kalsom; Ahmad, Norfadzilah; Mohd Mokhtar, Hanida Hani; Nurumal, Mohd Said (IIUM Press, 2023)
Introduction: Integration of soft skills components in clinical evaluation is essential for undergraduate nursing students. However, soft skills are a prerequisite for increasing confidence in providing services to patients. As future health professionals, these students must develop a complete set of competencies that go beyond technical competence. This paper is a report of a review conducted to identify, critically analyse and synthesize the integration of soft skills components in clinical evaluation for undergraduate nursing students Methods: A comprehensive literature search was carried out using databases EBSCO, ProQuest Dissertation and Theses, ProQuest Nursing Journal. An inclusion and exclusion criterion were identified. A narrative review of evidence- and non-evidence-based papers was conducted, using a relevant methodological framework with additional scrutiny of secondary data sources in the latter. Results: A total of 787 papers were identified, with 43 fully sourced and 17 included in the final review. There are three themes, which also provide a comprehensive understanding of the definition of soft skills component, the importance of soft skills among nursing students, and the outcomes and implications of soft skills in clinical assessment. Conclusion: Soft skills need to be incorporated into the nursing curriculum. The integration of soft skills elements in clinical skills assessment can improve the quality of nursing graduates and improve the quality of care and safety for patients.